ABORSI DALAM PERSPEKTIF HUKUM ISLAM (SUATU ANALISIS DENGAN PENDEKATAN FIQH AL-MUQÂRIN) - Jumat, Abd. Gani (Hunafa: Jurnal Studia Islamika, 2008)
Abortion is one of the contemporary law problems frequently debated. In Indonesia, abortion is not only a law problem but also a moral problem. Posing abortion within the law and moral perspective bocomes important since it is related to the law  dealing with the termination of a child’s right to life. This article deals with the status of  abortion within the Islamic law and moral perspective, employing the method of fiqh al-muqârin (comparative fiqh), that is by comparing and conforming the ikhtilâf of abortion amongst the jurists (fuqahâ’). After analyzing the jurists’ opinions of abortion, the writer found that since sperms and ovums come together and pertlization occurs, abortion is judged as a crime, and therefore the law status of which is proscribed.Kata Kunci:  aborsi, hukum Islam, moral